Resilience and Rights: Responding to Crime through a Human Rights Lens - Kanwel, Sidra; Khan, Muhammad Imran; Ahmad, Ishaq (Pakistan Journal of Humanities and Social Sciences, 2024)
Recently, a well-deserved attention was brought to the intersection between crime response and resilience as a human right. The paper explores the resilience concept within the domain of human rights, spotting the light on critical tendencies in crime and responses and reviewing the ‘human rights’ and ‘resilience’ perspectives. Shaping the principles and approaches of both, it implies that resilience and human rights perspectives should be applied simultaneously in criminal justice. The source provides an in-depth legal research analysis that helps to better understand the value and implications of such an approach. Overall, the notion defends the holistic and rights-centred approaches to crime processing.